Habitus and harmony: between the global and the local - Sadaka, Sami (2024)
The purpose of this paper is to add to existing literature on the nature of what is valued in the Big-4 accounting firms within their operations in non-Western settings, and how and why this relates to and reflects global and local influences, by investigating the situation in Lebanon within an Asian and Middle Eastern context. The paper demonstrates that the alignment of Big-4 practices with global practices is explained by the “internally constituted” historical and contextual circumstances which reflect the habitus of both locals generally, and actors who hold senior positions within the Big-4 firms. The extent of the tension or harmony between the global and the local helps explain why certain capitals are more valued in Big-4 firms within the context of emerging economies.